Studi Nutrisi Buah Ara (Ficus racemosa L.) untuk Pakan Ikan - Aryani, Netti; Zen, Zuhelmi; Syandri, Hafrijal; Jaswandi, Jaswandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
The purpose of the research was to find out the countent of nutrition of Ara (Ficus racemosa L) wich covers : thelevel of protein, fat, water, ash, fibrous part of the fruit, calcium, phosphor, vitamine C and E as well as amino acidwhich are very useful for enrichment of fish diets. The sample of Ara fruit were collected directly in the field. Therewere two types of processing Ara fruits used in this research, namely (1) cutting the fruits into thin layer and madeit into; (2) separating the fuit from the seed, dried, and made it into flour. The level of protein, fat, fibrous part of thefruit, water, and ash was analyzed by using proximate analysis, while the level of calcium was analyzed by usingAAS methods. The level of phosphor was measured by using spectrophotometer, the level of vitamine C and E wasanalyzed by using HPLC and amino acid by gas chromatography (CG). The study found that the flesh flour of Arafruit contained protein (10,63%), fat (8,66%), water (7,08 %), ash (11,57%), fibrous part of the fruit (16,15%), calcium514,88 mg/100 g), phosphor (418,29 mg/100 g), vitamine C (475,38 mg/100 g), and amino acid (3,013 %) higher thanAra flour with protein (8,98 %), fat (6,57%), water (10,26%), ash (18,23%), fibrous part of the fruit (20,31%), calcium(0,039 mg/100g), phosphor (0,002 mg/100g), vitamin C 25,48 mg/100 g ), and amino acid (1,24%). It can be concludedthat the Ara flour can be used as on of the ingredients for fish diets especially as the source of vitamine C, calciumand phosphor to incrase reproduction ability and growth.